The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1071/an16432
|View full text |Cite
|
Sign up to set email alerts
|

Tedera proves its value as a summer and autumn feed for sheep in Mediterranean-like climates

Abstract: Tedera (Bituminaria bituminosa C.H Stirt. vars. albomarginata and crassiuscula) is a traditional forage species for goats in the Canary Islands, Spain. It has agronomic characteristics ideally suited to Mediterranean-like climates that allows it to provide high quality green forage for grazing animals during summer and autumn. It can be used to extend the growing season into late spring and early summer and/or to reduce or eliminate the need for expensive hand feeding of grain and hay to sheep to fill the ‘fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…For example, Finlayson et al () report on an economically attractive perennial pasture species that was purposefully selected and bred to be highly adoptable by Australian farmers, with the aim of mitigating dryland soil salinity. It is expected that this new species will be sufficiently attractive to farmers to be widely adopted without the need for incentive payments (Real et al ), in the process improving soil quality as a spillover benefit.…”
Section: Considering Adoption In Agricultural Policymentioning
confidence: 99%
“…For example, Finlayson et al () report on an economically attractive perennial pasture species that was purposefully selected and bred to be highly adoptable by Australian farmers, with the aim of mitigating dryland soil salinity. It is expected that this new species will be sufficiently attractive to farmers to be widely adopted without the need for incentive payments (Real et al ), in the process improving soil quality as a spillover benefit.…”
Section: Considering Adoption In Agricultural Policymentioning
confidence: 99%
“…These Canarian varieties show higher CP and lower NDF and ADF content than Mediterranean rainfed grasslands, at a similar phenological stage (Henkin et al., 2011; Vázquez De Aldana et al., 2008; Zarovali et al., 2007). This higher nutritive value together with its drought and grazing tolerances make this species a promising fodder plant for Mediterranean grasslands (Oldham et al., 2013; Real et al., 2017; Sternberg et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in these varieties of B. bituminosa because of their drought resistance and good forage aptitude, especially BAM, which has been established as the most drought‐resistant variety (Martínez‐Fernández et al., 2012; Raeside et al., 2012). Its aptitude as a fodder plant in Mediterranean‐like climates has been tested in Australia and Israel, showing promising results (Oldham et al., 2013; Real et al., 2017; Sternberg et al., 2006). The large genetic diversity of B. bituminosa is a promising source for breeding programs (Foster et al., 2013; Pazos‐Navarro et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Four grazing experiments were conducted during summer and autumn in Western Australia from 2014 to 2017. These experiments demonstrated that tedera can be reliably grown as a monoculture and preserved as green pasture to be grazed directly by sheep or cattle to fill feed gaps and/or to reduce expensive supplementary feeding during summer and autumn [13].…”
Section: Introductionmentioning
confidence: 96%